History of economic analysis - Schumpeter, Joseph A. (New York : Oxford University Press, 1954)
At the time of his death in 1950, Joseph Schumpeter--one of the major figures in economics during the first half of the 20th century--was working on his monumental History of Economic Analysis. A complete history of humankind's theoretical efforts to understand economic phenomena from ancient Greece to the present, this book is an important contribution to the history of ideas as well as to economics.
Includes bibliographical references: p. 1205-1207. .
rpm 27/09/2017
Loans
Keywords: Economics; Economic analysis